2018
DOI: 10.15666/aeer/1603_35173528
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion Nets Influence on the Abundance of Ground Beetles (Coleoptera: Carabidae) in Apple Orchards

Abstract: Abstract. Ground beetles (fam. Carabidae) as beneficial insects are valuable organisms to study whether any of the new implemented agricultural measures in fruit production is beneficial. The aim of our study was to analyze impact of different types of exclusion nets on ground beetle species composition and abundance in an apple orchard. The study was conducted in an IPM apple orchard, situated in the northwest part of Croatia. The treatments for the study were four types of exclusion (colored) nets (Agritenax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As for diet contribution, beetles A. dorsalis were observed incorporating more plant-based resources in organically managed cereal fields than in the flowering fields (Mader et al 2018). The study (Pajač Živković et al 2018) showed the positive effect of exclusion nets on A. dorsalis in an apple orchard of Croatia, thus confirming their value in assessing the introduction of new agricultural measures into practice. Marrec et al (2017) evaluated the impact made on activity and density of A. dorsalis by local crops, current year, landscape composition, and their interaction, and inter-annual changes in landscape composition due to crop rotations.…”
Section: Discussionmentioning
confidence: 53%
“…As for diet contribution, beetles A. dorsalis were observed incorporating more plant-based resources in organically managed cereal fields than in the flowering fields (Mader et al 2018). The study (Pajač Živković et al 2018) showed the positive effect of exclusion nets on A. dorsalis in an apple orchard of Croatia, thus confirming their value in assessing the introduction of new agricultural measures into practice. Marrec et al (2017) evaluated the impact made on activity and density of A. dorsalis by local crops, current year, landscape composition, and their interaction, and inter-annual changes in landscape composition due to crop rotations.…”
Section: Discussionmentioning
confidence: 53%
“…Photoselective nets have also been used experimentally to manage codling moths in apple orchards, where they were also found to affect the abundance and species composition of orchard carabid communities: the highest total number of ground beetles was captured under yellow nets [89], but spider communities were not affected [90]. These results suggest that it may be possible to use photoselective nets to manipulate predator–prey ratios in favor of biological control, either in open field situations or in greenhouses.…”
Section: Opportunities: Factors Favoring Adoption and Development mentioning
confidence: 99%
“…The recent introduction of commercial solutions that enclose the entire orchard, known as "exclusion netting", has been tested for pest management purposes [10][11][12][13][14][15][16][17][18] in France, Italy and Croatia. More recently, this system was tested on apple physiology, on the early ripening Gala [9].…”
Section: Introductionmentioning
confidence: 99%